Covalently reactive microparticles imbibe blood to form fortified clots for rapid hemostasis and prevention of rebleeding - Ting Chen; Chaonan Xiao; Xianjun Chen; Ziyi Yang; Jingwei Zhao; Bingkun Bao; Qingmei Zeng; Li Jiang; Xinyi Huang; Yi Yang; Qiuning Lin; Wei Gong; et al. (Nature Communications)
Abstract Owing to the inherently gradual nature of coagulation, the body fails in covalently crosslinking to stabilize clots rapidly, even with the aid of topical hemostats, thus inducing hemostatic failure and potential rebleeding. Although recently developed adhesives confer sealing bleeding sites independently of coagulation, interfacial blood hampers their adhesion and practical applications. Here, we report a covalently reactive hemostat based on blood-imbibing and -crosslinking microparticles. Once contacting blood, the microparticles automatically mix with blood via imbibition and covalently crosslink with blood proteins and the tissue matrix before natural coagulation operates, rapidly forming a fortified clot with enhanced mechanical strength and tissue adhesion. In contrast to commercial hemostats, the microparticles achieve rapid hemostasis (within 30 seconds) and less blood loss (approximately 35 mg and 1 g in the rat and coagulopathic pig models, respectively), while effectively preventing blood-pressure-elevation-induced rebleeding in a rabbit model. This work advances the development and clinical translation of hemostats for rapid hemostasis and rebleeding prevention.